(In-)equality of Opportunity, Fairness, and Distributional Preferences - Dietmar Fehr; Daniel Müller; Marcel Preuss (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper examines how perceived importance of family background affect distributional pref-erences using two large-scale survey experiments. In the first experiment, we randomly inform respondents about the relationship between parental income and economic success later in life, which renders their perceptions of equality of opportunity more pessimistic. However, this changes neither revealed distributional preferences nor pro-social behavior toward the rich and poor. The second experiment shows that respondents do not account for parental influence on economic success when making (re-)distribution decisions, suggesting that people view parental influence as a legitimate reason to justify some inequality. This can explain why distributional preferences are immune to changes in perceptions of equality of opportunity.
Keywords: C93; D31; H23; H24; H41; 330; distributional preferences; inequality of opportunity; social mobility; survey experiment